2002
DOI: 10.1063/1.1429771
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculation of electron drift characteristics and avalanche noise in bulk InAs

Abstract: Field dependent drift velocity results are presented for electron transport in bulk indium arsenide (InAs) material based on a Monte Carlo model, which includes an analytical treatment of band-to-band impact ionization. Avalanche multiplication and related excess noise factor (F) are computed as a function of device length and applied voltage. A decrease in F with increases in device length is obtained. The results suggest an inherent utility for InAs-based single-photon avalanche detectors, particularly aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 66 publications
2
20
0
2
Order By: Relevance
“…Arguably, the work most comparable to this new experimental investigation is that of Satyanadh et al [21], who modeled avalanche multiplication in InAs at room temperature using a Monte Carlo model. Unfortunately, drawing comparisons with their results is difficult for two reasons.…”
Section: A Photomultiplication Characteristicsmentioning
confidence: 71%
See 2 more Smart Citations
“…Arguably, the work most comparable to this new experimental investigation is that of Satyanadh et al [21], who modeled avalanche multiplication in InAs at room temperature using a Monte Carlo model. Unfortunately, drawing comparisons with their results is difficult for two reasons.…”
Section: A Photomultiplication Characteristicsmentioning
confidence: 71%
“…This should make operation at high bit rates possible, even with wide depletion regions such as those characterized in this paper. Based on the saturated electron drift velocity modeled by Satyanadh et al [21] and the saturated hole drift velocity of In 0.53 Ga 0.47 As, the maximum bit rate achievable without intersymbol interference can be estimated. It is concluded that an InAs p-i-n diode with a 2.5-µm-wide intrinsic region could support bit rates up to ∼20 Gb/s.…”
Section: A Photomultiplication Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and 7 as a function of electric field. The MC results are compared with different experimental and theoretical data present in the literature [13,14,[42][43][44][45][46][47][48][49][50][51]. For an electric field lower than about 0.15 kV/cm, the velocity increases linearly and the carriers remain in the same valley (Fig.…”
Section: Drift Velocitymentioning
confidence: 98%
“…In a strong applied electric field, E, carriers can gain enough kinetic energy to ionize dopant impurities at low temperature [9][10][11] and/or to generate electron-hole pairs by interband impact ionization leading to avalanche breakdown [5,12,13], which greatly increases the conductivity. A magnetic field, B, applied perpendicular to the direction of the current flow, can strongly affect these impact ionization processes by increasing the binding energy of electrons bound onto impurities and hence the activation energy and electric field required for impurity ionization [9][10][11]; also, the Lorentz force exerted on the conduction electrons deflects the electron motion away from the direction of the electric field, effectively increasing the electric field required for excitation of electrons across the band gap.…”
Section: Introductionmentioning
confidence: 99%